ENERGY ANALYSIS OF MOBILE MACHINE VIBRATIONS - A. E. Pokatilov; V. I. Zagrevsky; D. A. Lavshuk (Наука и техника)
The paper considers mathematical models of a mobile machine movement and power expenses required for its motion. Initial data of the mobile machine parameters, results of computer-aided modeling of a soil road microstructure and distribution of released by vibrations are given in the paper.